2010
DOI: 10.1348/026151009x479042
|View full text |Cite
|
Sign up to set email alerts
|

Self‐paced study time as a cue for recall predictions across school age

Abstract: Recent work on metacognition indicates that monitoring is sometimes based itself on the feedback from control operations. Evidence for this pattern has not only been shown in adults but also in elementary schoolchildren. To explore whether this finding can be generalized to a wide range of age groups, 160 participants from first to eighth grade participated in a study based on a self-paced study time (ST) allocation paradigm. In contrast to previous studies, picture pairs instead of word pairs were used as sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
25
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 42 publications
7
25
0
1
Order By: Relevance
“…A follow-up study by the same authors (Koriat et al, 2009b) contrasting second and forth graders' performance in a setting which provided an unlimited number of trials to acquisition found evidence that even the younger participants were able to adopt the ELER-heuristic when items varied sufficiently in intrinsic difficulty. Hoffmann-Biencourt et al (2010) also confirmed this memorizing effort-heuristic with a similar self-paced learning task but different learning materials (picture pairs instead of word pairs) in a sample of children from grades 1 to 8. Yet, for first time, this study also documented a developmental trend in that it found a weaker relationship between ST and JOLs for younger children.…”
Section: Control Affects Monitoring-modelsupporting
confidence: 62%
See 2 more Smart Citations
“…A follow-up study by the same authors (Koriat et al, 2009b) contrasting second and forth graders' performance in a setting which provided an unlimited number of trials to acquisition found evidence that even the younger participants were able to adopt the ELER-heuristic when items varied sufficiently in intrinsic difficulty. Hoffmann-Biencourt et al (2010) also confirmed this memorizing effort-heuristic with a similar self-paced learning task but different learning materials (picture pairs instead of word pairs) in a sample of children from grades 1 to 8. Yet, for first time, this study also documented a developmental trend in that it found a weaker relationship between ST and JOLs for younger children.…”
Section: Control Affects Monitoring-modelsupporting
confidence: 62%
“…Previous research suggests that from the middle of the elementary school years on, children begin to successfully use the heuristic, the longer they study an item, the less likely they are to recall it, that is a CM-model (Koriat et al, 2009a;Hoffmann-Biencourt et al, 2010). Therefore, third-grade children were chosen as the youngest age group.…”
Section: The Present Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In three experiments, we found that processing fluency contributed to the relatedness effect. First, Experiment 1 showed that processing fluency as measured by number of trials to acquisition (e.g., Hoffmann-Biencourt et al, 2010;Koriat, 2008) contributed to the effect of relatedness on JOLs both for lists with uniformly strong associations and for lists with a wide range of associative strengths. Mediation analyses revealed that the indirect effect of relatedness on JOLs mediated by number of trials to acquisition explained up to 26 % of the total effect of relatedness on JOLs.…”
Section: Discussionmentioning
confidence: 99%
“…below: (1) the number of trials to acquisition in Experiment 1 (e.g., Hoffmann-Biencourt, Lockl, Schneider, Ackerman, & Koriat, 2010;Koriat, Ackerman, Lockl, & Schneider, 2009;Koriat, 2008) and (2) self-paced study time (e.g., Castel et al, 2007;Koriat, 2008;Koriat, Ma'ayan, & Nussinson, 2006;Miele, Finn, & Molden, 2011;Undorf & Erdfelder, 2011, 2013 in Experiments 2 and 3.…”
mentioning
confidence: 99%